Application of busness analytics methods in the organization of the recruitment process in technology startups - E. V. Vasileva; P. P. Pestryakov (Управление)
The purpose of this study is to show the capabilities of neural networks in the selection of personnel based on a specific set of characteristics and competencies necessary for solving design problems. Monitoring and filling professional gaps in organizations can be implemented using data analysis technologies, analytical methods. Within the framework of this work, the task is limited to finding personnel for technological entrepreneurship projects (startups). But this task can be expanded for the selection of personnel of any organization, including a set of indicators specific competencies, additional characteristics of staff, professional requirements, etc.The peculiarities of the problem to implement the business intelligence tools. A set of indicators for the selection of talents is defined. A set of criteria for evaluating candidates for project roles of the it project, including experience of project work, mentoring, availability of specialized certificate, knowledge of project methodology; ability to use analytical tools; knowledge of programming languages; sociability and conflict-free; ability to convince. The matrix of competences and powers on project roles is made. Among the competencies identified: basic, interpersonal, soft skills (soft skills) and additional skills through which the employee can replace colleagues in emergency cases.The functional scheme of the decision is constructed, and the neural network is realized, which displays connection of various attributes with the made decisions on them depending on values of the calculated criteria. As you import data on a few employees and gather information from hh.ru three candidates for the position, the calculation of compliance metrics to the selected positions.